Dynamic Optimum Design for the Gear Transmission System of the Lifting Mechanism of Mining Excavator - Peng Wei; Ni Liyong; Yu Chuhong (Jixie chuandong)
Taking the two stage gear transmission system of the lifting mechanism of a 300 kW mining excavator as study object,based on the gear dynamics theory,the multi objective dynamic optimization design is carried out on the basis of the simplified dynamics gear vibration model analysis,which aims at reducing the vibration and reducing the volume of the transmission system. By comparing and analyzing the dynamic characteristics of the system,the results obtained from the optimization design can meet the requirements of the system own strength,and at the same time,the quality and volume of the system are reduced.